2022
DOI: 10.1021/acs.macromol.2c00237
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Density-Specific Response of Grafted Polyelectrolytes to Electric Fields: Bending or Tilting?

Abstract: The response of polyelectrolytes (PEs) to applied electric fields drives applications in energetics, diagnostics, materials development, and many more. Here we employ allatom molecular dynamics (MD) simulations to probe the response of grafted PE brushes to axial electric fields. For PEs with large charge densities, the electric field triggers a left−right asymmetric distribution of counterions around the PE backbone: consequently, depending on the location (left or right), there is an unequal screening and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…While there has been significant experimental, [19][20][21][22][23] theoretical, [24][25][26][27][28][29][30] and simulation [31][32][33][34] studies focused on probing such responsiveness and behavior of the PE molecules as functions of the water and ion properties, a pinpointed atomistic understanding of the behavior of the brush supported water molecules and ions has remained very limited. Only recently, there have been efforts to study the PE brushes and the brush supported ions and water molecules using all-atom molecular dynamics (MD) simulations: [35][36][37][38][39][40] the utility of such an approach is that they provide unprecedented fundamental understanding about the atomistic structure, properties, and behaviors of brushsupported ions and water molecules, which in turn can be leveraged for a variety of potential applications (such as coion-driven electroosmotic transport 41 and simultaneous energy harvesting and flow augmentation 42 in PE brush functionalized nanochannels).…”
Section: Introductionmentioning
confidence: 99%
“…While there has been significant experimental, [19][20][21][22][23] theoretical, [24][25][26][27][28][29][30] and simulation [31][32][33][34] studies focused on probing such responsiveness and behavior of the PE molecules as functions of the water and ion properties, a pinpointed atomistic understanding of the behavior of the brush supported water molecules and ions has remained very limited. Only recently, there have been efforts to study the PE brushes and the brush supported ions and water molecules using all-atom molecular dynamics (MD) simulations: [35][36][37][38][39][40] the utility of such an approach is that they provide unprecedented fundamental understanding about the atomistic structure, properties, and behaviors of brushsupported ions and water molecules, which in turn can be leveraged for a variety of potential applications (such as coion-driven electroosmotic transport 41 and simultaneous energy harvesting and flow augmentation 42 in PE brush functionalized nanochannels).…”
Section: Introductionmentioning
confidence: 99%
“…The electric field reduces the overall brush height [see Figure b]. The mechanism of the electric-field-mediated brush height reduction for the case of PAA PE brushes has been discussed in our recent paper . The axial electric field introduces an asymmetry in the structure of the complex formed between the PAA PE monomer and the counterion bound (condensed) to the PAA PE monomer: this complex gets oriented in the direction of the applied electric field .…”
Section: Resultsmentioning
confidence: 99%
“…This particular nature of the ion distribution (OS of the PE brush layer) meant an excess of coions in the brush-free bulk (as the system needed to be electroneutral), enforcing a most remarkable coion-dominated EOS transport. However, an increase in the electric field strength led to a brush height reduction (we described the detailed mechanism of such reduction in a follow-up paper) and disappearance of the OS effect, eventually triggering a counterion-dictated EOS transport (therefore, we also encounter an electric-field-strength-mediated reversal of EOS flow direction). In another study, we showed that such OS effect and the consequent coion-dominated EOS transport can be leveraged to trigger a most interesting electroslippage effect (which refers to simultaneous electrokinetic energy generation and flow augmentation) in the presence of an applied pressure-driven flow in such brush-functionalized nanochannels.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations